Photoactivity of hierarchically nanostructured ZnO–PES fibre mats for water treatments. Issue 49 (29th April 2016) - Ognibene, G.; Cristaldi, D. A.; Fiorenza, R.; Blanco, I.; Cicala, G.; Scirè, S.; Fragalà, M. E.
Abstract : Brush-like ZnO nanorods shell grown by CBD onto electrospun PES fibres as photocatalytic membranes for water purification. Abstract : A brush-like ZnO nanorods shell is grown by Chemical Bath Deposition on electrospun Zn(Ac)2 doped polyethersulfone fibres. The obtained mats are water resistant and photocatalytically active, thus resulting suitable for applications in water purification. The used procedure is simple, cost-effective and scalable to large volumes. The use of supported ZnO nanostructures onto fibrous mats paves the way to easily reusable photocatalyst that benefits the high surface area of nanostructures and limits the drawbacks associated to the use of nanoparticles and nanopowders ( i.e. water turbidity, irradiation efficiency and photocatalyst recover), thus resulting suitable for use in membrane technology.